Menelisik Dimensi Esoteris Al-Qur’an dalam Penafsiran Sufistik ‘Ā’ishah Al-Bā‘ūnīyah - Syamsuri, Syamsuri (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2023)
This paper explores the esoteric interpretations of the Qur’an as expounded by ‘Ā‘ishah al-Bā‘ūnīyah, a notable 16th century female Sufi teacher, through her seminal work Al-Muntakhab fī Uṣūl al-Rutab fī ‘Ilm al-Taṣawwuf. Despite her non-mufasir status, ‘Ā‘ishah’s significant influence on Sufism thought is evident, particularly in her adept utilization of Qur’anic verses to fortify various Sufi concepts. This study unveils ‘Ā‘ishah’s thematic methodology in interpreting the Qur’an, demonstrating her reliance on Qur’anic signs and correlation-based approaches. Importantly, her esoteric interpretations align harmoniously with the literal meanings of the verses, adhere to Islamic jurisprudence, and are supported by robust arguments, including hadith and the consensus of classical Muslim scholars. This research underscores the intellectually grounded contributions of ‘Ā‘ishah al-Bā‘ūnīyah to Sufi thought, highlighting the compatibility of esoteric interpretations within the broader Islamic framework.